2020
DOI: 10.1080/16549716.2020.1809841
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of a mobile phone health survey for risk factors for noncommunicable diseases in Colombia: a qualitative study

Abstract: Background: Data collection on noncommunicable disease (NCD) behavioral risk factors has traditionally been carried out through face-to-face surveys. However, its high costs and logistical difficulties can lead to lack of timely statistics for planning, particularly in low and middle-income countries. Mobile phone surveys (MPS) have the potential to fill these gaps. Objective: This study explores perceptions, feasibility and strategies to increase the acceptability and response rate of health surveys administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…Most of the participants in this study (CATI–IVR) were people between 18 years old and 44 years old. The previous finding is consistent with the results from prior research conducted in Colombia, which explored the perception and feasibility of implementing MPS 32. That study found that respondents perceive these types of surveys as inconvenient since they can take a long time and interfere with their daily activities since the CATI survey was implemented during business hours (08:00–17:00) and took about 23 min to complete the survey.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Most of the participants in this study (CATI–IVR) were people between 18 years old and 44 years old. The previous finding is consistent with the results from prior research conducted in Colombia, which explored the perception and feasibility of implementing MPS 32. That study found that respondents perceive these types of surveys as inconvenient since they can take a long time and interfere with their daily activities since the CATI survey was implemented during business hours (08:00–17:00) and took about 23 min to complete the survey.…”
Section: Discussionsupporting
confidence: 89%
“…The IVR survey involved a series of pre-recorded questions in Spanish. 32 The audios were professionally recorded by a nationally recognised female journalist and then loaded onto a self-service platform, engageSPARK. 33 The survey response options were programmed to be answered using the mobile phone keypad.…”
Section: Methodsmentioning
confidence: 99%
“…An earlier study has pointed to a direct relationship between convenience and increased acceptability especially by older adults [ 43 ]. In few studies there are divergent findings regarding time and day preferences for phone-based surveys [ 41 , 44 ], but the option of data collectors speaking to interviewees to schedule convenient interview times appears to offer a favourable approach. Many participants stated their appreciation for the perceived privacy offered by the telephone interview, in relation to being able to speak when they were alone or with minimal intrusion.…”
Section: Discussionmentioning
confidence: 99%
“…Though this view was not universal, some respondents would be willing to have a longer interview if the subject of discussion is relevant to them. Studies including this study have reported varied perceptions about what respondents thought would constitute appropriate time for a phone interview [ 38 , 44 , 45 ]. Telephone interview respondents are more likely to complain about the phone interview duration than respondents in face-to-face interview, possibly owing to the social distance and the different dynamics between the two data collection modes [ 38 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the widespread access to mobile phones globally and rapidly expanding capabilities of digital devices, mobile technology is increasingly finding a place in monitoring communicable and noncommunicable diseases, and their associated risk factors [5][6][7]. Simple mobile phone surveys (MPS) deployed through live operator administered interviews, pre-recorded automated interactive voice response (IVR) surveys, or automated text messaging have recently been trialed to facilitate large-scale population monitoring of NCD risk factors in Colombia, Uganda, and other countries [8][9][10][11][12]. What makes these efforts particularly attractive to policymakers, public health practitioners, and researchers is their relatively low cost, minimal technological requirements, and potential to cut data collection and processing times down from year(s) to weeks [5,7].…”
Section: Introductionmentioning
confidence: 99%